Distinct perturbations of oral squamous cell carcinoma patients: A quantitative cytomorphometric analysis - Sharma, Deepti; Sandhu, Simarpreet V; Bansal, Himanta; Gupta, Shruti (International Journal of Health Sciences, 2015)
Objective: Oral cancer constitutes a major health issue in developing countries, representing the leading cause of death. Quantitative assessment by sophisticated diagnostic techniques is becoming increasingly important. Hence, a histochemical staining procedure and morphometric evaluation is used to obtain optimal information on the cellular events. The objective of present study is to assess the variation in cellular area, nuclear area, cellular diameter, nuclear diameter and nuclear/cytoplasmic ratio respectively in normal subjects, smokeless tobacco users smokers, combination and oral squamous cell carcinoma patients. Methods: Total 125 number of individual were divided into five groups, each comprising 25 individuals of more than 40 years of age. These groups were: a. Normal, b. smokeless tobacco users, c. smoking d. combination and e. oral squamous cell carcinoma.’ Oral smears were obtained, stained with Feulgen stain and the cells were measured cytomorphometrically using Nikon imaging software. Results: Our study showed a significant reduction in the cellular diameter, cellular area and increase in the nuclear diameter, nuclear area and nuclear/ cytoplasmic ratio in oral squamous cell carcinoma patients as compared to tobacco users and normal patient. Significant changes were found in group I, II, III and IV when compared with group V but as such no significant inter-group variation was found in cellular and nuclear dimensions in smokers, smokeless tobacco users, combination and control group. Conclusion: Quantitative parameters could be assessed by cytomorphometry. Cytomorphological changes in exfoliated squames could serve as a useful adjunct in the early diagnosis of oral squamous cell carcinomas. Keywords: Cancer Cytomorphometry; Exfoliative cytology; Feulgen reaction; Imaging software; Papanicolaou stain; Premalignant lesion; Tobacco.